2014
DOI: 10.4049/jimmunol.1400160
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Human IgA1 and IgA2 Autoantibodies to Type VII Collagen Induce Subepidermal Blistering Ex Vivo

Abstract: Subepidermal autoimmune blistering dermatoses (AIBD) are prototypic autoantibody-mediated diseases. In epidermolysis bullosa acquisita (EBA), an autoimmune disease with severe and chronic skin blistering, autoantibodies are directed against type VII collagen. IgG is the predominant autoantibody isotype of EBA, the pathogenicity of which has been demonstrated in a variety of in vivo and ex vivo disease models. In contrast, there is not much evidence for the pathogenicity of IgA, which may appear as the only aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

5
4

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 62 publications
0
27
0
Order By: Relevance
“…Based on this insight, the pathogenic relevance of COL7 autoantibodies has been demonstrated (i) in vitro by demonstrating digestion of the dermal–epidermal junction in skin specimen incubated with anti-COL7 IgG or IgA and neutrophils (378, 379), (ii) in vivo by induction of inflammation and blistering in mice by transfer of anti-COL7 IgG (380, 381) or by immunization (382, 383), and (iii) clinically by the observation of a correlation of circulating autoantibody titers with clinical disease severity (384, 385). Subsequently, use of these animal models has greatly contributed to our current understanding of EBA pathogenesis.…”
Section: Autoantibody-induced Inflammationmentioning
confidence: 99%
“…Based on this insight, the pathogenic relevance of COL7 autoantibodies has been demonstrated (i) in vitro by demonstrating digestion of the dermal–epidermal junction in skin specimen incubated with anti-COL7 IgG or IgA and neutrophils (378, 379), (ii) in vivo by induction of inflammation and blistering in mice by transfer of anti-COL7 IgG (380, 381) or by immunization (382, 383), and (iii) clinically by the observation of a correlation of circulating autoantibody titers with clinical disease severity (384, 385). Subsequently, use of these animal models has greatly contributed to our current understanding of EBA pathogenesis.…”
Section: Autoantibody-induced Inflammationmentioning
confidence: 99%
“…The pathogenicity of different IgG subclasses, as well as IgA directed against COL7, still remains a controversial issue: although some data suggest a potential of IgG4 to induce subepidermal splits ex vivo (Mihai et al, 2007), others have demonstrated opposite findings (Recke et al, 2010). Furthermore, IgA has recently been demonstrated to lead to subepidermal splits ex vivo (Recke et al, 2014;van der Steen et al, 2012). On the basis of the developed animal model here, these findings can now be addressed in vivo to investigate the potential pathogenic contribution of IgA, as well as IgG subclasses in EBA.…”
Section: Discussionmentioning
confidence: 91%
“…Accordingly, several non-MHC quantitative trait loci linked to specific chromosomes that control susceptibility to EBA could be identified (Ludwig et al, 2012). Although these genetic data were derived from immunization-induced EBA, variations in skin blistering between mouse strains were also Incubation of cryosections of human skin with anti-COL7 antibodies (patient serum, total patient IgG, affinity-purified patient IgG, or monoclonal anti-COL7 IgG or IgA) and isolated human polymorphonuclear leukocytes or neutrophils Recke et al, 2010Recke et al, , 2014Sitaru et al, 2002 In vivo antibody transfer-induced EBA mouse model…”
Section: Pathophysiologic Events and Emerging Treatmentsmentioning
confidence: 99%
“…Multiple lines of evidence show that anti-COL7-NC1 autoantibodies are pathogenetically relevant in EBA: (i) circulating autoantibodies parallel disease activity in patients (Kim et al, 2013;Saleh et al, 2011), (ii) transplacental autoantibody transfer causes transient skin blistering in the newborn (Abrams et al, 2011), (iii) autoantibodies recruit and activate leukocytes ex vivo, resulting in dermal-epidermal separation in human skin cryosections (Recke et al, 2010(Recke et al, , 2014Sitaru et al, 2002), and (iv) injection of antibodies against COL7 or (v) immunization with autoantigen leading to autoantibody production in mice results in skin inflammation that duplicates important aspects of the human disease, especially the inflammatory (bullous pemphigoid-like) EBA variant (antibody transferand immunization-induced EBA, respectively; Table 1). Pathogenicity may not be limited to the skin, as mucosal morbidity in EBA patients as well as autoantibody-induced intestinal inflammation and weight loss in mice with experimental EBA associated with alterations in metabolic pathways similar to those found in inflammatory bowel diseases has been described Luke et al, 1999;Schö nig et al, 2013).…”
Section: Introductionmentioning
confidence: 99%